If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 9x + 9 Reorder the terms: -3 + 4x = 9x + 9 Reorder the terms: -3 + 4x = 9 + 9x Solving -3 + 4x = 9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 4x + -9x = 9 + 9x + -9x Combine like terms: 4x + -9x = -5x -3 + -5x = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -5x = 9 + 0 -3 + -5x = 9 Add '3' to each side of the equation. -3 + 3 + -5x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 9 + 3 -5x = 9 + 3 Combine like terms: 9 + 3 = 12 -5x = 12 Divide each side by '-5'. x = -2.4 Simplifying x = -2.4
| 5x^3-3x^2-5x+3=5x^2-4x-1 | | y=[100+.75(y-150)]+100+100 | | 2v^2-3v+1=0 | | (x^2)+(11x)=0 | | y=-16+4x | | y=4x+-16 | | 2x+20=60+x | | 4(3x+7)=16 | | x^2-4x^2+3=0 | | (x^2)-(6x)=0 | | (4x^2+2x)(5x-4)= | | -1.5x+y=5 | | (x^2)-(6x)=o | | (5x-3)(x+1)(x-1)=0 | | 3x-6=5x+60 | | 5y+7=2y+11 | | -13+2x=-52+35x(fraction) | | 10a+b=8a+8b | | 43x+7=16 | | (5x-3)(x+1)(x-1)=(5x+1)(5x-1)x | | 7000=(1+0.0425t) | | 58-2x=8-7x | | 2(y-9)=3Y-8 | | 4(2x-3)-7x+5=11 | | 4x+2x+9+x+4=34 | | (2x+2)(3x^2-x+2)= | | -3(1)-3= | | y=[100+.75(y-100)]+100+100 | | -8s+32=54 | | .66x+7=39 | | -9s+14=21 | | 2.4=0.3x+0.4y |